2016
DOI: 10.1088/0953-8984/28/41/414015
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional systems with competing interactions: dynamic properties of single particles and of clusters

Abstract: Systems with short-range attractive and long-range repulsive interactions are able to form mesophases at sufficiently low temperatures. In two dimensions, such mesophases emerge as clusters, stripes or bubbles. Using extensive Monte Carlo simulations we investigate the static and the dynamic properties of such a cluster-forming system over a broad temperature range and for different densities. Via the static properties we analyse how ordering into close packed configurations sets in both at the level of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Indeed we are only aware of a few studies in which fluids with competing interactions confined between parallel plates were studied, but those were restricted to two-and one-dimensional cases [20,28,29]. The literature on the dynamic behaviour of fluids with competing interactions in confinement is also scarce [30].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed we are only aware of a few studies in which fluids with competing interactions confined between parallel plates were studied, but those were restricted to two-and one-dimensional cases [20,28,29]. The literature on the dynamic behaviour of fluids with competing interactions in confinement is also scarce [30].…”
Section: Introductionmentioning
confidence: 99%
“…In certain models, this feature has been identified with the onset of clustering, whose trend it generally follows. 14,[82][83][84] In order to assess this relationship, we separately consider the clustering properties of Eq. ( 1) as detailed in Sec.…”
Section: Discussionmentioning
confidence: 99%
“…The generated self-assembled structures have applications in medicine, self-driven molecules, catalysis, photonic crystals, stable emulsions, biomolecules and self-healing materials [24]. Experiments [25] and simulations [26,27] showed that in the case of spherical colloids the mechanism behind the formation of these distinct patterns is the presence of competitive interactions. These com-peting forces can appear from the combination of a short range attraction of the core and a long-range repulsion [28] of the grafted polymers [29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%